Review on the correlation between mixing, microstructure and strength of cementitious products with nanoparticles. Issue 1 (July 2021) - Adithya, S N; Sachin, K C; Radhakrishna,; Meda, Ujwal Shreenag
Abstract: Concrete is manmade multiphase composite where coarse granular materials are embedded in a hard matrix of binder, filling the space between the aggregate particles and gluing them all together that strengthens with time on hydration. Addition of nanoparticles further enhances the properties of the concrete such as early strength, refined micro structure and enhanced durability. Nanoparticles are added to cementitious composites by dry mixing with cement or dispersion in water. The challenge associated with it is the uniform dispersion of the nanoparticles in the matrix of the composite. The type of mixer and the mixing pattern affect the fresh and hardened properties of the concrete. This article reviews the effect of dispersion of nano particles, type of mixer and mixing pattern on the properties of cementitious composites.